Coronary Artery Diseases During Pregnancy: Minimizing Adverse Consequences and Improving Clinical Outcome - Haque, Nadira; Hosain, Nazmul; Islam, AKM Monwarul; Mamataz, Zakia; Md Ibrahim, -; Ahmed, Shamim; Md Anisuzzaman, -; Akter, Shahena (Cardiovascular Journal, 2021)
Coronary artery disease in pregnancy is a catastrophic situation that may endanger the lives of both the mother and the fetus. Cardiac diseases may account for up to 15% of maternal mortality. Pregnancy may increase the risk of acute myocardial infarction up to 4-fold. Various hemodynamic derangements may occur during pregnancy including expansion of plasma and blood volume, compression of inferior vena cava and fall in both systemic and pulmonary vascular resistances. If pregnant women present with acute coronary artery disease, medical management should be attempted first and if any intervention or surgery is needed, efforts must be made to lower the risk. A multidisciplinary approach is essential involving obstetrician, cardiologist, cardiac surgeons, anesthesiologist and neonatologists or pediatrician. Pregnancy is considered to be a relative contraindication to thrombolytic therapy due to some complications. Revascularization may be considered in acute coronary syndrome in pregnant women like other nonpregnant patients. Primary per cutaneous coronary intervention or coronary artery bypass graft have been performed successfully during pregnancy and may be considered as therapeutic option in pregnancy in selective cases. Percutaneous coronary intervention (PCI) is considered to be relatively safe for maternal and fetal survival during pregnancy. Main worry in PCI is radiation exposure and need to dual antiplatelet therapy. Bare metal stent is preferred during pregnancy because of shorter duration of anticoagulation therapy. Early second trimester is the optimum surgical period to coronary artery bypass surgery (CABG) in pregnant women. Coronary artery bypass surgery can be safely done after 28 weeks of gestational age and immediately after cesarean section. Early detection, a multidisciplinary approach and timely interventions must be considered in coronary artery disease in pregnancy for better obstetric outcome. Cardiovasc j 2021; 14(1): 61-69